Employee Satisfaction and Related Factors among Public Healthcare Workers in Sri Lanka: A Case Study on Regional Directorate of Hambanthota (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: health work force; employee satisfaction; two factor theory of harzburg